Utility of Whole Genome Sequencing for Population Screening of Deafness-Related Genetic Variants and Cytomegalovirus Infection in Newborns - Xiang, Jiale; Zhang, Hongfu; Sun, Xiangzhong; Zhang, Junqing; Xu, Zhenpeng; Sun, Jun; Peng, Zhiyu (Frontiers in Genetics, 2022)
Background: Hearing loss affects approximately 2 out of every 1000 newborns. Genetic factors and congenital cytomegalovirus (CMV) infections account for around 90% of the etiology. The purpose of this study was to develop and test a whole genome sequencing (WGS) approach to detect deafness-related genetic variants and CMV infections simultaneously in newborns. Method: Deafness-related genes causing congenital or childhood hearing loss were curated and selected for newborn screening. Nine dried blood spots from newborns with known genetic variants (n=6) or CMV infections (n=3) were employed to develop and validate the WGS testing and analytic pipeline. We then pilot tested the WGS analysis on 51 de-identified clinical samples. Results: 92 gene-disease pairs were selected for screening hearing loss in newborns. In the validation test, WGS accurately detected all types of genetic variants, including single nucleotide variations, insertions/deletions, and copy number variations in the nuclear or mitochondrial genome. Sequence reads mapping to the CMV reference genome were discovered in CMV infected samples. In the pilot test, WGS identified 9 out of 51 (18%) newborns carrying pathogenic variants associated with deafness. Additionally, two newborns (4%, 2/51) had pathogenic variants in LDLR and APOB causing familial hypercholesterolemia as secondary findings. Conclusions: WGS can simultaneously detect genetic variants and CMV infections in dried blood spot specimens from newborns. Our study provides proof of principle that genome sequencing can be a promising alternative for newborn screening of hearing loss.